Novel polymer supported graphene and molybdenum sulfide as highly efficient cocatalyst for photocatalytic hydrogen evolution. (27th September 2018) - Mu, Haiyan; Wan, Junfen; Wu, Yuanwang; Xu, Juan; Wang, Le; Cao, Xuejun
Abstract: Exploiting photocatalysts with environmental friendliness, noble-metal-free and high efficiency is a great challenge for photocatalytic hydrogen evolution. In this work, we synthesized a novel MoS2 /rGO/Cd0.6 Zn0.4 S composite catalyst based on microsphere-structural polymer with highly efficient photocatalytic activity under visible light irradiation. The 5.0%MoS2 /rGO/Cd0.6 Zn0.4 S exhibited the highest H2 evolution rate of 11.7 mmol/h/g, which about 2.1 times higher than that without MoS2 and 4 times higher than that without PSGM. This superior photocatalytic activity, further demonstrated by the transient photocurrent responses and electrochemical impedance spectrum, was attributed to the effective separation of the photo-generated charge carriers promoted by the positive synergetic effect between the MoS2 and graphene. This study provided a promising approach to achieve high-efficiency H2 evolution based on graphene and MoS2 without noble metals. Highlights: A polymer supported structure for novel MoS2 /rGO/Cd0.6 Zn0.4 S composite catalyst. 5%MoS2 /rGO/Cd0.6 Zn0.4 S exhibited the highest H2 production rate of 11.7 mmol/h/g. The positive synergetic effect between the MoS2 and graphene.